Learning curve analysis for duodenal endoscopic submucosal dissection: A single‐operator experience. Issue 11 (13th September 2022) - Ozeki, Yuichiro; Hirasawa, Kingo; Sawada, Atsushi; Ikeda, Ryosuke; Nishio, Masafumi; Fukuchi, Takehide; Kobayashi, Ryosuke; Sato, Chiko; Maeda, Shin
Abstract: Background and Aims: Superficial duodenal epithelial tumors are emerging targets for endoscopic submucosal dissection (ESD). However, it is unknown how competence is achieved in duodenal ESD. This study aimed to elucidate the learning curve for duodenal ESD. Methods: This retrospective observational study included 100 consecutive patients who underwent duodenal ESD by a single endoscopist between March 2014 and September 2021. The primary outcome was to define the learning curve for duodenal ESD by an endoscopist with sufficient non‐duodenal ESD experience. Cumulative sum (CUSUM) curve analysis was used to assess the learning curve in terms of procedural speed. Comparative analyses of phases identified using the CUSUM method were performed. Results: In total, 98 patients were included in the analysis. Evaluation of the cumulative sum curve revealed four distinct phases in the graph: phase I, cases 1–25 (learning phase); phase II, cases 26–47 (proficiency phase); phase III, cases 48–72 (mastery phase); and phase IV, cases 73–98 (after introduction of general anesthesia). The median procedural speed was significantly faster in phase II than in phase I (11.1 mm 2 /min vs 7.0 mm 2 /min, P = .002). Clinically significant intraoperative perforation tended to decrease through phase II to phase IV (22.7%, 12.0%, and 3.8% in phases II, III, and IV, respectively). Delayed perforation occurred only in phases I and II. Conclusions: Duodenal ESD requires 25 cases to gain proficiency and 50 to achieve mastery even for an endoscopist with extensive non‐duodenal ESD experience.